Global Strategy for the Diagnosis, Management and Prevention of Chronic Obstructive Lung Disease 2017 Report: GOLD Executive Summary. Issue 3 (7th March 2017) - Vogelmeier, Claus F.; Criner, Gerard J.; Martinez, Fernando J.; Anzueto, Antonio; Barnes, Peter J.; Bourbeau, Jean; Celli, Bartolome R.; Chen, Rongchang; Decramer, Marc; Fabbri, Leonardo M.; Frith, Peter; Halpin, David M.G.; et al.
ABSTRACT: This Executive Summary of the Global Strategy for the Diagnosis, Management and Prevention of COPD, Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2017 Report focuses primarily on the revised and novel parts of the document. The most significant changes include: (i) the assessment of chronic obstructive pulmonary disease has been refined to separate the spirometric assessment from symptom evaluation. ABCD groups are now proposed to be derived exclusively from patient symptoms and their history of exacerbations; (ii) for each of the groups A to D, escalation strategies for pharmacological treatments are proposed; (iii) the concept of de‐escalation of therapy is introduced in the treatment assessment scheme; (iv)non‐pharmacological therapies are comprehensively presented and (v) the importance of co‐morbid conditions in managing COPD is reviewed.